"Artistic and Aesthetic Values of Graphic Art In the Artistic Production of Students in the Department of Art Education" (Journal of the College of Basic Education, 2025)
This research aims to reveal the artistic and aesthetic value of graphic art in the artistic output of students In the Department of Art Education, through analyzing the extent of students’ understanding of this non-traditional art form and how they employ its elements and techniques in their visual artworks. The study Is based on the hypothesis that incorporating the concepts and methods of graffiti art Into the educational process may contribute to the development of students’ artistic sensibility and visual expression, opening up new horizons for creativity.The research adopts a descriptive-analytical methodology, analyzing samples of students’ artworks before and after being exposed to this art form, In addition to a questionnaire measuring their attitudes and impressions toward it. The results showed that graphic art enhanced boldness in expression and allowed students to use contemporary symbols and logos. It also helped improve their skills In composition, as well as the use of color and line.The research recommends integrating the concepts of graphic art into the curricula of art education departments, as an effective means of fostering creativity and enhancing visual communication with societal issues